Efeitos do digital no trabalho do luto: uma análise discursiva e psicanalítica em perfis memoriais do Facebook - Cesário, Guilherme Beraldo (2021)
This dissertation proposes to analyze the effects of digital in the symbolic work of elaboration of mourning in publications remembered from memorial profiles on Facebook. Anchored in the theoretical assumptions of French Discourse Analysis, represented especially by the name of Michel Pêcheux and Eni Orlandi, and some theoretical precepts of Psychoanalysis by Freud and Lacan, our objective is to understand the effects of the proper functioning of the digital, via profiles Facebook memorials and their excesses of meanings promote the work of mourning and its rituals, also considering the game between memory and forgetting placed in these memorial profiles that actively circulate in the digital medium, governed by the functions of the heir. The affects of grief are understood by Freud (2013 [1915-1917]), similar to that of melancholy. Metaphorically, the author says that, both in mourning and in melancholy, there is an open wound, however, in the work of mourning, this wound becomes a scar: the work of mourning ends. In melancholy, this wound does not close. Whereas the memorial profile constantly provides the return of the image and profile of the deceased, making it difficult to heal this wound, which approaches melancholy, at the same time, the digital offers symbolic tools, such as writing, for this wound to be embroidered and healed. While Facebook's memorial allows for an (eternal) return of the dead to the feeds, it also provides tools for the symbolic operations, which embroider the real hole caused by the death, that contribute to the completion of the mourning work. There is no conclusion in this dissertation, but considerations that open up new research. This work was carried out with the support of the Cordenação de Aperfeiçoamento de Pessoal de Nível Superor – Brasil (CAPES) – Financing Code 001